C10 Generation and characterisation of a transgenic rat model of huntington's disease-like 4 (HDL4), also called spinocerebellar ataxia type 17 (SCA17). (29th August 2012) - Kelp, A; Koeppen, AH; Petrasch-Parwetz, E; Calaminus, C; Bauer, C; Bauer, P; Riess, O; Nguyen, HP
Abstract : Huntington's disease-like 4 (HDL4), also called spinocerebellar ataxia type 17, is an autosomal-dominant, late-onset neurodegenerative disorder caused by CAG repeat expansions in the TATA-box-binding protein (TBP), an ubiquitously expressed transcription factor. The clinical features of HDL4 closely resembled those of Huntington's disease, including uncontrolled movements, emotional problems, and loss of thinking ability. To further investigate this devastating disease and additionally find a good model for treatment studies, we generated the first transgenic rat model of HDL4, which carries a full human cDNA fragment of the TBP gene with 64 CAG repeats under the control of the murine prion protein promoter (PrP-TBP64Q). In total we obtained ten positive founder animals, whereof only five transmitted the transgene. On the basis of the expression level of mutant TBP as well as the distribution of mutant TBP in the different brain regions we chose one of these five lines (line 8.4) for further characterisation. This line shows a strong expression of the mutant TBP protein in the cerebellum and a moderate expression in the olfactory bulb, brainstem and cortex. HDL4 rats showed an ataxia-like phenotype and impaired motor coordination and balance capabilities in the beam walking test. Additionally, HDL4 rats had a significantly lower body weight than their wildtype littermates and showed decreased activity. At the age of 10 months neuropathological changes, such as misshaped Purkinje cells, degenerated dendrites as well as missing basket and stellate neurons were observed in the cerebellum of heterozygous transgenic HDL4 rats compared to wildtype littermates. By electron microscopy we demonstrated dark cell degeneration as well as moderate fibre degeneration in the striatum. Moreover, we observed decreased levels of dopamine receptor (D2 R) by performing PET imaging. Altogether the present data shows that this animal model exhibits symptoms which mimic well the human HDL4 phenotype indicating that this rat model will be of great value for further studies of pathomechanisms in Huntington's disease-like 4 and for therapeutic trials.